Brief Report: Retrospective Evaluation on the Efficacy of Lopinavir/Ritonavir and Chloroquine to Treat Nonsevere COVID-19 Patients. (1st October 2020) - Gao, Guiju; Wang, Aibin; Wang, Sa; Qian, Fang; Chen, Meiling; Yu, Fengting; Zhang, Ju; Wang, Xudong; Ma, Xiaoyang; Zhao, Tianwei; Zhang, Fujie; Chen, Zhihai
Abstract : Background: The effectiveness of lopinavir/ritonavir (LPV/r) and chloroquine treatment for COVID-19 has not been verified. Methods: We conducted a retrospective study to summarize the clinical practices of nonsevere patients with COVID-19 receiving the standard care, LPV/r or chloroquine in Beijing Ditan Hospital from January 20 to March 26, 2020. The main outcome measurements include the changes of cycle threshold values of open reading frame 1 ab (ORF1ab) and nucleocapsid (N) genes by reverse transcriptase–polymerase chain reaction assay from day 1 to 7 after admission for patients receiving standard care or after treatment being initiated for patients receiving either LPV/r or chloroquine. The proportion of developing severe illness, fever duration and the time from symptom onset to chest computer tomography improvement, and negative conversion of nucleic acid were compared. Results: Of the 129 patients included in the study, 59 received the standard care, 51 received LPV/r, and 19 received chloroquine. The demographics and baseline characteristics were comparable among the 3 groups. The median duration of fever, median time from symptom onset to chest computer tomography improvement, and negative conversion of the nucleic acid were similar among the 3 groups. The median increase in cycle threshold values of N and ORF1ab gene for patients receiving LPV/r or chloroquine or the standard care during the treatment course was 7.0 and 8.5, 8.0, and 7.6, 5.0, and 4.0, respectively. These figures were not found significantly different among the 3 groups. Conclusions: Antiviral therapy using LPV/r or chloroquine seemed not to improve the prognosis or shorten the clinical course of COVID-19.